2017
DOI: 10.1016/j.cmet.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Sites and Mechanisms Linking Reduction of Dipeptidyl Peptidase-4 Activity to Control of Incretin Hormone Action and Glucose Homeostasis

Abstract: Pharmacological inhibition of the dipeptidyl peptidase-4 (DPP4) enzyme potentiates incretin action and is widely used to treat type 2 diabetes. Nevertheless, the precise cells and tissues critical for incretin degradation and glucose homeostasis remain unknown. Here, we use mouse genetics and pharmacologic DPP4 inhibition to identify DPP4 cell types essential for incretin action. Although enterocyte DPP4 accounted for substantial intestinal DPP4 activity, ablation of enterocyte DPP4 in Dpp4 mice did not produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(132 citation statements)
references
References 38 publications
6
124
1
1
Order By: Relevance
“…10, 31-35). The circulating Ex-4 level in our system (~4 ng/ml) was much higher than the basal plasma GLP-1 level in mice (48,49) or healthy humans (50) but close to the therapeutic concentration target for GLP-1R agonists in clinical use (36). The duration of Ex-4 infusion in our study was shorter (28 days) Table 1 for the quantification of TUNEL + β cells in PBS+saline-treated, Ex-4+saline-treated, PBS+FK506-treated, and Ex-4+FK506-treated graft samples from 3 juvenile donors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…10, 31-35). The circulating Ex-4 level in our system (~4 ng/ml) was much higher than the basal plasma GLP-1 level in mice (48,49) or healthy humans (50) but close to the therapeutic concentration target for GLP-1R agonists in clinical use (36). The duration of Ex-4 infusion in our study was shorter (28 days) Table 1 for the quantification of TUNEL + β cells in PBS+saline-treated, Ex-4+saline-treated, PBS+FK506-treated, and Ex-4+FK506-treated graft samples from 3 juvenile donors.…”
Section: Discussionmentioning
confidence: 94%
“…Juvenile islets were isolated at the Institute of Cellular Therapeutics of the Allegheny Health Network (Pittsburgh, Pennsylvania, USA) as previously described (3,4,26). Islets from 12 adult donors (ages 20,21,29,30,40,43,43,48,49,53,60, and 60 years, BMI ranges 24.1-29.6) were obtained from the Integrated Islet Distribution Program (http://iidp.coh.org). Islet function (i.e., glucose-induced insulin secretion) was assessed by islet perifusion assay on the day of arrival, as previously described (57,58).…”
Section: Methodsmentioning
confidence: 99%
“…In 2011, Waget et al described how inhibition of DPP-4 activity in the intestine was involved in regulating glycaemia [7]. Recently, Mulvihill et al demonstrated that glucose tolerance depended on inhibition of DPP-4 activity in haematopoietic and endothelial cells, but there was no involvement of the DPP-4 expressed by enterocytes [8]. DPP-4 activity modulates the functionality of more than 40 potential substrates, including cytokines, chemokines and growth factors, some of which are particularly relevant for gut homeostasis [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that in obese mice, oral DPP4 inhibitors function by inhibiting gut endothelial DPP4 23 . We tested the hypothesis that oral DPP4 inhibition and hepatocyte DPP4 silencing have fundamentally different effects on adipose inflammation and glucose metabolism: we directly compared treatment with the oral DPP4 inhibitor sitagliptin with silencing of hepatocyte DPP4 in DIO mice.…”
mentioning
confidence: 99%